Semântica proposicional categórica - Ferreira, Rodrigo Costa (2010)
The basic concepts of what later became called category theory were introduced in 1945 by Samuel Eilenberg and Saunders Mac Lane. In 1940s, the main applications were originally in the fields of algebraic topology and algebraic abstract. During the 1950s and 1960s, this theory became an important conceptual framework in other many areas of mathematical research, especially in algrebraic homology and algebraic geometry, as shows the works of Daniel M. Kan (1958) and Alexander Grothendieck (1957). Late, questions mathematiclogics about the category theory appears, in particularly, with the publication of the Functorial Semantics of Algebraic Theories (1963) of Francis Willian Lawvere. After, other works are done in the category logic, such as the the current Makkai (1977), Borceux (1994), Goldblatt (2006), and others. As introduction of application of the category theory in logic, this work presents a study on the logic category propositional. The first section of this work, shows to the reader the important concepts to a better understanding of subject: (a) basic components of category theory: categorical constructions, definitions, axiomatic, applications, authors, etc.; (b) certain structures of abstract algebra: monoids, groups, Boolean algebras, etc.; (c) some concepts of mathematical logic: pre-order, partial orderind, equivalence relation, Lindenbaum algebra, etc. The second section, it talk about the properties, structures and relations of category propositional logic. In that section, we interpret the logical connectives of the negation, conjunction, disjunction and implication, as well the Boolean connectives of complement, intersection and union, in the categorical language. Finally, we define a categorical boolean propositional semantics through a Boolean category algebra.